2012
DOI: 10.1002/ijc.27775
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival benefits for irinotecan‐containing regimens as first‐line treatment for advanced gastric cancer: An updated meta‐analysis of ten randomized controlled trials

Abstract: The standard treatment for patients with advanced gastric cancer (AGC) is still debated, and the available data on the benefit of irinotecan-containing regimen as first-line treatment for those patients are controversial. We performed a systematic review and meta-analysis of randomized controlled trials to determine the survival benefits of irinotecan-containing regimens in this setting. A total of 1,837 patients from ten trials were included in the analysis. Our results showed that irinotecan-containing regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Additionally, statistically similar overall RR was observed in two meta-analyses [51, 52]. Another one found similar objective RR between two groups [35]. One meta-analysis did not report relevant data.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Additionally, statistically similar overall RR was observed in two meta-analyses [51, 52]. Another one found similar objective RR between two groups [35]. One meta-analysis did not report relevant data.…”
Section: Resultssupporting
confidence: 56%
“…When it comes to OS, three of them demonstrated that the survival was statistically similar [51, 52, 59] while one meta-analysis favored CPT-11-containing therapy in terms of OS but the 1-year survival rate did not show significant difference between two groups [35]. Additionally, statistically similar overall RR was observed in two meta-analyses [51, 52].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations